Does Automatic Speech Recognition (ASR) Have a Role in the Transcription of Indistinct Covert Recordings for Forensic Purposes? - Loakes, Debbie (Frontiers in Communication, 2022)
The transcription of covert recordings used as evidence in court is a huge issue for forensic linguistics. Covert recordings are typically made under conditions in which the device needs to be hidden, and so resulting speech is generally indistinct, with overlapping voices and background noise, and in many cases the acoustic record cannot be analysed via conventional phonetic techniques. Resulting transcripts that are produced, often by police working on the case, are often questionable and despite their unreliable nature can be provided as evidence in court. Injustices can, and have, occurred. Given the growing performance of automatic speech recognition (ASR) technologies, a common question asked is whether ASR can solve the problem of what was said in indistinct forensic audio, and this is the focus of the current paper. The aim of this research is to demonstrate how automatic transcription systems fare with forensic-like audio , and with more than one system. Examples are given of how various ASR systems cope with indistinct audio, showing that when a good quality recording is used ASR systems cope well and the resulting transcript is usable and, for the most part, accurate. When a poor-quality, forensic-like recording is used, on the other hand, the resulting transcript is effectively unusable, with numerous errors and very few words recognised (and in some cases, no words recognised). Forced alignment is also analysed, and it is shown that it appears to work, but inaccuracies abound. This research shows that the way things currently stand, computational methods are not suitable for solving the issue of transcription of indistinct forensic audio for a range of reasons. Such systems cannot transcribe what was said in indistinct covert recordings, and nor can they determine who uttered the words and phrases in such recordings. These systems can indeed be used advantageously in research, and for various other purposes, and the reasons they do not work for forensic transcription stems from the nature of the recording conditions, as well as the nature of the forensic context.